Bumetanide reduces seizure frequency in patients with temporal lobe epilepsy. Issue 1 (12th October 2012) - Eftekhari, Sanaz; Mehvari Habibabadi, Jafar; Najafi Ziarani, Massoumeh; Hashemi Fesharaki, Seyed Sohrab; Gharakhani, Marzieh; Mostafavi, Hossein; Joghataei, Mohammad Taghi; Beladimoghadam, Nahid; Rahimian, Elham; Hadjighassem, Mahmoud Reza
Summary Alterations in the balance of K‐Na‐2Cl cotransporter (NKCC1) and Na‐Cl cotransporter (KCC2) activity may cause depolarizing effect of γ‐aminobutyric Acid (GABA), and contribute to epileptogenesis in human temporal lobe epilepsy. NKCC1 facilitates accumulation of chloride inside neurons and favors depolarizing responses to GABA. In the current pilot study we provide the first documented look at efficacy of bumetanide, a specific NKCC1 antagonist, on reduction of seizure frequency in adult patients with temporal lobe epilepsy. According to our results, seizure frequency was reduced considerably in these patients. Furthermore, epileptiform discharges decreased in two of our patients. If the efficacy of bumetanide is proven in large scale studies, it can be used as a supplemental therapy in temporal lobe epilepsy.